Домантівське городище в гирлі р. Супій - Прядко, О.О. (Археологія і давня історія України, 2021)
Стаття присвячена результатам пошукових
археологічних досліджень 2015—2017 рр. на території с. Домантове Золотоніського району Черкаської області (село відселене в кінці 1950-х рр. у
зв’язку з будівництвом Кременчуцького водосховища). Проаналізовано матеріали виявлені, як на території городища так і найближчої округи. Подано детальний опис археологічної пам’ятки. Розглянута теза про можливий варіант локалізації літописної Дубниці у гирлі р. С упій. Наведено аналогії з найближчими фортецями Переяславської землі
в гирлах річок Трубіж та Сула — відповідно літописні містечка Устя і Воїнь. The paper is devoted to the results of exploratory
archaeological research in 2015—2017 in the Domantovo
village of Zolotonosha district of Cherkasy region
(the village was resettled in the late 50s of the XX century
due to the construction of the Kremenchuh reservoir).
The author considered the thesis about the
possible variant of localization of the chronicle Dubnytsia
at the mouth of the Supii River. The chronicle
city is mentioned in the chronicle in 1155 in the events
connected with the Cumans arrival in the Pereiaslav
region. N. P. Barsov, M. O. Maksymovych, V. H. Liaskoronskyi,
O. M. Andriyashev, L. E. Makhnovets
versions of localization of the chronicle Dubnytsia are
analyzed. Detailed description of the hillfort and the
fortified suburb (posad) is provided. Archaeological
materials discovered on the territory of the site were
analyzed not only by the author, but also by other researchers
(M. F. Ponomarenko and V. F. Pocheptsov).
Finds of Old Rus time from the site are presented in
the exhibitions of Zolotonosha and Domantovo museums.
The localization, discovery and introduction into
scientific circulation of the previously unknown site
would hardly possible without a detailed manuscript
plan of Danylo de Bosket made in 1746. The ancient
hillfort is marked in the center of the castle near the
Supii River in the form of dominant round hill. Today,
the moats from the castle and the suburb (posad) are
almost invisible visually but they are clearly visible on
satellite images.
The detailed description of the topographic situation
is provided, according to which the advantage of the
waterway over overland in the Domantovo microregion
becomes clear.
The analogies with the nearest fortresses of the
Pereiaslav region in the mouths of the Trubizh and the
Sula rivers are provided — respectively the chronicle
towns of Ustia and Voin. In addition Domantovo hillfort
was the part of the Dnipro defensive line, which
included the «Serpent’s Wall» the moat of which faces
the Dnipro River. Research results indicate that the
Domantovo hillfort arose at the beginning of the XI century,
and in the middle of the XII century already represented
a significant fortified settlement at the Supii
mouth which also served as a pier on the Dnipro-Supii
waterways of Pereiaslav region.